Case Report: Intercurrent infections in COVID-19-induced sustained immunodepression: is interferon gamma a suitable drug? - De Waard, Aurianne; Lefebvre, Laurent; Textoris, Julien; Payen, Didier (Frontiers in Immunology, 2023)
Acute immuno-depression syndrome (AIDS) had been found in many life-threatening conditions and was associated to recurrent secondary infections. We report 1 COVID-19 severe ARDS treated by interferon  (INF) after a long delay of failure of antibiotic treatment to control superinfections. The response to INF was evaluated by the flowcytometry HLA-DR expression on circulating monocytes. This response was compared to a non-COVID-19 ARDS patient presenting also an AIDS, treated with INF. Both were responder to INF with no apparent difference in INF response between the 2 mechanisms of lung primary injury induced-ARDS.